Indium Tin Oxide–Based Fully Spray‐Coated Inverted Solar Cells with Nontoxic Solvents: The Role of Buffer Layer Interface on Low‐Bandgap Photoactive Layer Performance. Issue 5 (14th April 2019) - Polino, Giuseppina; Dell'Elce, Simone; Liscio, Andrea; La Notte, Luca; Cardone, Giorgio; Di Carlo, Aldo; Brunetti, Francesca
Abstract : In bulk heterojunction solar cells, the morphology of the interfaces between the photoactive layer (PAL) and charge transporting layers during the deposition process plays a key role in achieving high‐efficiency devices. Herein, an inverted fully spray‐coated solar cell fabricated on an indium tin oxide (ITO)‐glass substrate is presented. It is demonstrated that a spray‐coated double electron transporting layer composed of zinc oxide (ZnO) nanoparticles coated with polyethylenimine ethoxylated (PEIE) improves the morphology of the spray‐coated active layer on top of the spray‐coated cathode. Moreover, focusing on the hole transporting layer and anode, the performance obtained using a commercial poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) blend is compared with a high‐conductive anhydrous PEDOT:PSS (A‐PEDOT) mixed with a commercial PEDOT:PSS (CPP‐105D) as transporting layer. By optimizing the spray deposition of all the layers, a fully scalable spray process is used to produce polymer solar cells with ITO/ZnO/PEIE/poly[[4, 8‐bis[(2‐ethylhexyl)oxy]benzo[1, 2‐b:4, 5‐b']dithiophene‐2, 6‐diyl] [3‐fluoro‐2‐ [(2‐ethylhexyl)carbonyl] thieno[3, 4‐b]thiophenediyl]] (PTB7): [6, 6]‐phenyl‐C70‐butyric‐acid‐methyl‐ester (PC70BM)/CPP:A‐PEDOT structure, achieving a power conversion efficiency (PCE) of 3.6%. Such result is significant if compared to a spray‐coated structure with evaporated anode (MoO3 ‐Ag). In this case (ITO/ZnO/PEIE/PTB7:PCBM/MoO3 ‐Ag), a power conversion efficiency of 5.5% is obtained. Abstract : The devices produced using poly(3, 4‐ethylenedioxythiophene):poly(styrenesul‐fonate) (PEDOT:PSS) blend as top electrode are compared with the devices prepared using a high‐conductive anhydrous PEDOT:PSS (A‐PEDOT) formulation developed in our laboratory. By optimizing the spray deposition of all the layers, a fully scalable spray process has been used to produce inverted polymer solar cells with ITO/ZnO/PEIE/PTB7:PCBM/CPP:A‐PEDOT structure, achieving a power conversion efficiency of 3.6%.